Facile Synthesis and Characterization of SrCO3/MgO/CaO/CaCO3 Novel Nanocomposite for Efficient Removal of Crystal Violet Dye from Aqueous Media - Ehab A. Abdelrahman; Maram T. Basha (Inorganics)
Crystal violet dye poses significant environmental and human health risks due to its toxicity, persistence, and bioaccumulative nature. It contributes to potential carcinogenicity, cytotoxicity, and systemic toxicity upon human exposure. To address this issue, a novel SrCO3/MgO/CaO/CaCO3 nanocomposite was synthesized using the Pechini sol-gel method, producing AE500 and AE700 at 500 and 700 °C, respectively, for the efficient removal of crystal violet dye from aqueous media. X-ray diffraction (XRD) analysis confirmed the formation of crystalline phases, with average crystallite sizes of 64.53 nm for AE500 and 75.34 nm for AE700. Energy-dispersive X-ray spectroscopy (EDX) revealed elemental compositions with variations in carbon, oxygen, magnesium, calcium, and strontium percentages influenced by synthesis temperature. Field-emission scanning electron microscopy (FE-SEM) showed morphological differences, where AE500 had irregular polyhedral structures, while AE700 exhibited more compact spherical formations, with average grain sizes of 99.98 and 132.23 nm, respectively. High-resolution transmission electron microscopy (HR-TEM) confirmed the structural integrity and nano-scale morphology, showing aggregated irregularly shaped particles in AE500, while AE700 displayed well-defined polyhedral and nearly spherical nanoparticles. The calculated average particle diameters were 21.67 nm for AE500 and 41.19 nm for AE700, demonstrating an increase in particle size with temperature. Adsorption studies demonstrated maximum capacities of 230.41 mg/g for AE500 and 189.39 mg/g for AE700. The adsorption process was exothermic, spontaneous, and physical, following the pseudo-first-order kinetic model and Langmuir isotherm, indicating monolayer adsorption onto a homogenous surface.